MOCVD growth and structural characterization of In–Sb–Te nanowires. Issue 2 (17th September 2015) - Selmo, S.; Cecchi, S.; Cecchini, R.; Wiemer, C.; Fanciulli, M.; Rotunno, E.; Lazzarini, L.; Longo, M.
Abstract : In this work, the self‐assembly of In3 Sb1 Te2 and In‐doped Sb4 Te1 nanowires (NWs) for phase change memories application was achieved by metal organic chemical vapor deposition, coupled with vapor–liquid–solid (VLS) mechanism, catalyzed by Au nanoparticles. Single crystal In3 Sb1 Te2 and In‐doped Sb4 Te1 NWs were obtained for different reactor pressures at 325 °C. The parameters influencing the NW self‐assembly were studied and the compositional, morphological, and structural analysis of the grown structures was performed, also comparing the effect of the used substrate (crystalline Si and SiO2 ). In both cases, NWs of several micrometer in length and with diameters as small as 15 nm were obtained.